1991
DOI: 10.1126/science.1650033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Assembly of the Tyrosyl Radical-Dinuclear Iron Cluster Cofactor of Ribonucleotide Reductase

Abstract: Incubation of the apoB2 subunit of Escherichia coli ribonucleotide reductase with Fe2+ and O2 produces native B2, which contains the tyrosyl radical-dinuclear iron cluster cofactor required for nucleotide reduction. The chemical mechanism of this reconstitution reaction was investigated by stopped-flow absorption spectroscopy and by rapid freeze-quench EPR (electron paramagnetic resonance) spectroscopy. Two novel intermediates have been detected in the reaction. The first exhibits a broad absorption band cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
493
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(513 citation statements)
references
References 30 publications
16
493
4
Order By: Relevance
“…Similarly, Mn(II) ions have been used to probe the mechanism of metal ion incorporation in the homodimeric diiron-dependent RNR [83][84][85][86]. Hendrich and coworkers used CW EPR data acquired at X-and Q-band frequencies to show that binding of a single Mn(II) ion to one of the domains of apo-RNR induced a significant allosteric event that prevented binding of an additional equivalent of Mn(II) to the other domain.…”
Section: Past Studiesmentioning
confidence: 99%
“…Similarly, Mn(II) ions have been used to probe the mechanism of metal ion incorporation in the homodimeric diiron-dependent RNR [83][84][85][86]. Hendrich and coworkers used CW EPR data acquired at X-and Q-band frequencies to show that binding of a single Mn(II) ion to one of the domains of apo-RNR induced a significant allosteric event that prevented binding of an additional equivalent of Mn(II) to the other domain.…”
Section: Past Studiesmentioning
confidence: 99%
“…Moreover, single (35) and multiple turnover (36,38) studies of what is generally believed to approximate the chain length of the physiological substrate, eicosanoic acid (EA), have indicated that oxidative decarboxylation, affording nonadecene, is the largely dominant reaction route (34). Combined 13 C substrate and H 2 18 O 2 isotopic labeling by our laboratory has shown that cleavage of the terminal fatty acid carboxylate does not lead to recovery of 18 …”
mentioning
confidence: 99%
“…Despite the ubiquity of this mechanism, in some metalloenzymes, a metal−oxo species is formed that is not ultimately destined for incorporation into a substrate. Some characterized examples include the nonheme dinuclear iron ribonucleotide reductase (RNR R2) (18,19) and mononuclear iron halogenase SyrB2 (20-22). The mechanisms for RNR and SyrB2 highlight the importance of quaternary structural elements, an extensive 35-Å proton-coupled electron transfer pathway in RNR (23), and extremely subtle (subangstrom) substrate positional tuning (SyrB2) (21,22), to enable efficient circumvention from the monooxygenation reaction coordinate.…”
mentioning
confidence: 99%
“…The function of the metal site appears to be the generation and stabilization of the radical (7)(8)(9)(10). Protein R2 having the tyrosyl radical reduced to normal tyrosine is called Met-R2 (R2 Met ) and is enzymatically inactive.…”
mentioning
confidence: 99%